2021
DOI: 10.1111/fare.12595
|View full text |Cite
|
Sign up to set email alerts
|

“Stop going in my room”: A grounded theory study of conflict among stepsiblings

Abstract: Objective: This research explores how, and under what conditions, stepsiblings engage in, manage, and resolve conflict. Background: Interpersonal conflict is widely recognized as a meaningful and consequential relational dynamic. Although stepfamily conflict has been studied in a variety of family contexts (e.g., spousal, parent-child, stepparentstepchild), conflict among stepsiblings has received scant attention. The growing prevalence of stepsiblings, coupled with the role of conflict in shaping family dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Consistent with qualitative investigations about how individuals manage stepfamily relationships (Ganong et al, 2011; Ganong et al, 2019; Landon et al, 2022), we found that adolescents developed three distinct strategies to deal with ambiguous family relationships: improving relationships, accepting ambiguity, and creating distance. This heterogeneity in how the participants tried to handle ambiguity highlights that individuals have agency in dealing with ambiguity, even though it is emotionally difficult to handle it.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with qualitative investigations about how individuals manage stepfamily relationships (Ganong et al, 2011; Ganong et al, 2019; Landon et al, 2022), we found that adolescents developed three distinct strategies to deal with ambiguous family relationships: improving relationships, accepting ambiguity, and creating distance. This heterogeneity in how the participants tried to handle ambiguity highlights that individuals have agency in dealing with ambiguity, even though it is emotionally difficult to handle it.…”
Section: Discussionsupporting
confidence: 86%
“…Ambiguity in relations with other step‐relatives might be the result of similar mechanisms. For example, stepsiblings may be distant if they dislike each other from the start (Ganong, Sanner, et al, 2022), thus fail to establish a meaningful connection (Landon et al, 2022), or perceive differential treatment by their (step)parents (Noller, 2005). Therefore, children might find it difficult to clarify unknowns about them.…”
Section: Introductionmentioning
confidence: 99%
“…Youth perceptions of parent–child ties indicate less closeness, warmth, and parental involvement after remarriage (Day & Acock, 2004; McLanahan & Sandefur, 1994). Many stepchildren worry about and are sensitive to perceived changes in their relationships with parents when parents repartner, describing fear, jealousy, and sadness over perceptions that parent–child relationships have taken a back seat to their parents' efforts to nurture bonds with new partners and their partners' children (Cartwright, 2005; Landon et al, 2022). Although parents may feel that they are successfully sharing their time between children, new partners, and new stepchildren, children may have very different perceptions of the changing nature of parent–child bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We explored how stepparents develop close relationships with stepchildren, identifying factors that facilitate stepparents' efforts to bond with stepchildren and finding that close stepparent‐stepchild relationships promote marital quality and stepfamily cohesion (Ganong, Jensen, Sanner, Russell, & Coleman, 2019; Ganong, Jensen, Sanner, Russell, Chapman, & Coleman, 2019; Ganong et al, 2020). We explored relationship development among half‐ and stepsiblings, illuminating the perspectives of younger half‐siblings and exploring how stepsiblings manage conflict and develop close ties (Ganong, Landon, et al, 2022; Landon et al, 2022; Sanner, Russell, et al, 2018). In a series of projects, we conducted systematic reviews of the literature about what works in stepfamilies, distilling research evidence about actions employed by parents and stepparents that are linked to children's positive outcomes (Ganong et al, 2022a, 2022b, 2022c, 2022d; Sanner et al, 2022).…”
Section: Part Ii: Professional Perspectivesmentioning
confidence: 99%